Question Number 59282 by Mr X pcx last updated on 07/May/19 | ||
$${calculate}\:{f}\left({x}\right)=\int_{\mathrm{0}} ^{\infty} \:\:{e}^{−{x}\left[{t}\right]} {sin}\left(\left[{t}\right]\right){dt} \\ $$ $${with}\:{x}>\mathrm{0} \\ $$ $$\left.\mathrm{2}\right)\:{calculate}\:\int_{\mathrm{0}} ^{\infty} \:\:{e}^{−\mathrm{3}\left[{t}\right]} {sin}\left(\left[{t}\right]\right){dt}\:. \\ $$ | ||
Commented bymaxmathsup by imad last updated on 08/May/19 | ||
$$\left.\mathrm{1}\right)\:{we}\:{have}\:{f}\left({x}\right)\:=\sum_{{n}=\mathrm{0}} ^{\infty} \:\int_{{n}} ^{{n}+\mathrm{1}} \:{e}^{−{nx}} \:{sin}\left({n}\right)\:{dt}\:=\sum_{{n}=\mathrm{0}} ^{\infty} \:\:{sin}\left({n}\right){e}^{−{nx}} \left({n}+\mathrm{1}−{n}\right) \\ $$ $$=\sum_{{n}=\mathrm{0}} ^{\infty} \:\:{e}^{−{nx}} \:{sin}\left({n}\right)\:={Im}\left(\:\sum_{{n}=\mathrm{0}} ^{\infty} \:{e}^{−{nx}+{in}} \right)\:\:{but} \\ $$ $$\sum_{{n}=\mathrm{0}} ^{\infty} \:\:{e}^{−{nx}\:+{in}} \:=\sum_{{n}=\mathrm{0}} ^{\infty} \:\:\left({e}^{{i}−{x}} \right)^{{n}} \:\:=\frac{\mathrm{1}}{\mathrm{1}−{e}^{{i}−{x}} }\:=\frac{\mathrm{1}}{\mathrm{1}−{e}^{−{x}} \left({cos}\left(\mathrm{1}\right)+{isin}\left(\mathrm{1}\right)\right.} \\ $$ $$=\frac{\mathrm{1}}{\mathrm{1}−{e}^{−{x}} {cos}\left(\mathrm{1}\right)−{i}\:{e}^{−{x}} {sin}\left(\mathrm{1}\right)}\:=\frac{\mathrm{1}−{e}^{−{x}} {cos}\left(\mathrm{1}\right)+{ie}^{−{x}} {sin}\left(\mathrm{1}\right)}{\left(\mathrm{1}−{e}^{−{x}} {cos}\left(\mathrm{1}\right)\right)^{\mathrm{2}} \:+{e}^{−\mathrm{2}{x}} {sin}^{\mathrm{2}} \left(\mathrm{1}\right)}\:\Rightarrow \\ $$ $${f}\left({x}\right)\:=\frac{{e}^{−{x}} {sin}\left(\mathrm{1}\right)}{\left(\mathrm{1}−{e}^{−{x}} {cos}\left(\mathrm{1}\right)\right)^{\mathrm{2}} \:+{e}^{−\mathrm{2}{x}} {sin}^{\mathrm{2}} \left(\mathrm{1}\right)}\:=\frac{{e}^{−{x}} {sin}\left(\mathrm{1}\right)}{\mathrm{1}−\mathrm{2}\:{e}^{−{x}} {cos}\left(\mathrm{1}\right)\:+{e}^{−\mathrm{2}{x}} } \\ $$ $$\left.\mathrm{2}\right)\:\int_{\mathrm{0}} ^{\infty} \:\:\:{e}^{−\mathrm{3}\left[{t}\right]} {sin}\left(\left[{t}\right]\right){dt}\:={f}\left(\mathrm{3}\right)\:=\frac{{e}^{−\mathrm{3}} {sin}\left(\mathrm{1}\right)}{{e}^{−\mathrm{6}} \:−\mathrm{2}{e}^{−\mathrm{3}} {cos}\left(\mathrm{1}\right)+\mathrm{1}}\:=\frac{{e}^{\mathrm{3}} {sin}\left(\mathrm{1}\right)}{\mathrm{1}−\mathrm{2}{e}^{\mathrm{3}} {cos}\left(\mathrm{1}\right)\:+{e}^{\mathrm{6}} }\:. \\ $$ | ||
Answered by tanmay last updated on 07/May/19 | ||
$${f}\left({x}\right)=\int_{\mathrm{0}} ^{\mathrm{1}} {e}^{−{x}×\mathrm{0}} {sin}\left(\mathrm{0}\right){dt}+\int_{\mathrm{1}} ^{\mathrm{2}} {e}^{−{x}×\mathrm{1}} {sin}\left(\mathrm{1}\right){dt}+ \\ $$ $$\int_{\mathrm{2}} ^{\mathrm{3}} {e}^{−{x}×\mathrm{2}} {sin}\left(\mathrm{2}\right){dt}\:+...+\int_{{r}} ^{{r}+\mathrm{1}} {e}^{−{x}×{r}} {sin}\left({r}\right){dt}+... \\ $$ $$=\mathrm{0}+{e}^{−{x}} {sin}\mathrm{1}+{e}^{−\mathrm{2}{x}} {sin}\mathrm{2}+{e}^{−\mathrm{3}{x}} {sin}\mathrm{3}+... \\ $$ $$=\underset{{r}=\mathrm{0}} {\overset{\infty} {\sum}}{e}^{−{rx}} ×{sinr} \\ $$ $$ \\ $$ $${Q}={e}^{−{x}} {sin}\mathrm{1}+{e}^{−\mathrm{2}{x}} {sin}\mathrm{2}+{e}^{−\mathrm{3}{x}} {sin}\mathrm{3}+... \\ $$ $${P}={e}^{−{x}} {cos}\mathrm{1}+{e}^{−\mathrm{2}{x}} {cos}\mathrm{2}+{e}^{−\mathrm{3}{x}} {cos}\mathrm{3}+... \\ $$ $${P}+{iQ}={e}^{−{x}} ×{e}^{{i}} +{e}^{−\mathrm{2}{x}} ×{e}^{{i}\mathrm{2}} +{e}^{−\mathrm{3}{x}} ×{e}^{{i}\mathrm{3}} +... \\ $$ $${S}={t}+{t}^{\mathrm{2}} +{t}^{\mathrm{3}} +...\infty\:\:\:\:\left[{t}=\frac{{e}^{{i}} }{{e}^{{x}} }\right] \\ $$ $${S}=\frac{{t}}{\mathrm{1}−{t}}=\frac{{e}^{{i}} }{{e}^{{x}} \left(\mathrm{1}−\frac{{e}^{{i}} }{{e}^{{x}} }\right)}=\frac{{cos}\mathrm{1}+{isin}\mathrm{1}}{{e}^{{x}} −{cos}\mathrm{1}−{isin}\mathrm{1}} \\ $$ $${S}=\frac{\left({cos}\mathrm{1}+{isin}\mathrm{1}\right)}{\left({e}^{{x}} −{cos}\mathrm{1}\right)^{\mathrm{2}} +{sin}^{\mathrm{2}} \mathrm{1}}×\left({e}^{{x}} −{cos}\mathrm{1}+{isin}\mathrm{1}\right) \\ $$ $${S}=\frac{{cos}\mathrm{1}\left({e}^{{x}} −{cos}\mathrm{1}\right)+{isin}\mathrm{1}{cos}\mathrm{1}+{isin}\mathrm{1}\left({e}^{{x}} −{cos}\mathrm{1}\right)−{sin}^{\mathrm{2}} \mathrm{1}}{{e}^{\mathrm{2}{x}} −\mathrm{2}{e}^{{x}} {cos}\mathrm{1}+\mathrm{1}} \\ $$ $$=\frac{{e}^{{x}} {cos}\mathrm{1}−\mathrm{1}+{i}\left({sin}\mathrm{1}{cos}\mathrm{1}+{e}^{{x}} {sin}\mathrm{1}−{sin}\mathrm{1}{cos}\mathrm{1}\right)}{{e}^{\mathrm{2}{x}} −\mathrm{2}{e}^{{x}} {cos}\mathrm{1}+\mathrm{1}} \\ $$ $${so}\:{reauired}\:{ans}\:{is}\:{Q}\:=\left({complex}\:{part}\right) \\ $$ $$=\frac{{e}^{{x}} {sin}\mathrm{1}}{{e}^{\mathrm{2}{x}} −\mathrm{2}{e}^{{x}} {cos}\mathrm{1}+\mathrm{1}} \\ $$ $${pls}\:{check}\:... \\ $$ $$\left.\mathrm{2}\right)\frac{{e}^{\mathrm{3}} {sin}\mathrm{1}}{{e}^{\mathrm{6}} −\mathrm{2}{e}^{\mathrm{3}} {cos}\mathrm{1}+\mathrm{1}} \\ $$ $$ \\ $$ $$ \\ $$ | ||
Commented bymaxmathsup by imad last updated on 08/May/19 | ||
$${sir}\:{Tanmay}\:{your}\:{answer}\:{is}\:{correct}\:{thanks}... \\ $$ | ||
Commented bytanmay last updated on 08/May/19 | ||
$${most}\:{welcome}\:{sir} \\ $$ | ||